Las personas jurídicas como sujeto de protección de los derechos de autor por obras creadas bajo relación de dependencia en el código orgánico de la economía social de los conocimientos, creatividad e innovación - Oñate Piza, Geminis Neidi (2020)
This research project entitled "Legal entities as a subject of copyright protection for works created under a dependency relationship in the Organic Code of the Social Economy of Knowledge, Creativity and Innovation" develops a General Objective that aims to: Analyze the Ownership of legal persons on copyright in works created under a dependency relationship, considering that fictitious persons assume investment risks, through an investigation of the Organic Code of the Social Economy of Knowledge, Creativity and Innovation. And five Specific Objectives: 1. To study whether legal persons are reality or legal fictions, and whether they can be creative subjects of an intellectual work, making a comparative analysis of international regulations; 2. Determine the legal consequences of the entry into force of the Ingenios Code in the exercise of the intellectual rights of legal persons in Ecuador regarding their investigative movements in the national territory; 3. Valuing the constitutional guarantees of the right to exercise intellectual property and the right to work, from the granting of authorship to legal persons in works created under a dependency relationship in the national territory; and, 4. Analyze if it is appropriate to propose a reform to the Organic Code of the Social Knowledg Economy,…………..